Orbital Oscillator Commutation Relations and Mass Shifting for Superstring - Loan, Nguyen Thi Ha; Ha, Nguyen Hong (Communications in Physics, 2009)
In this work we extend the results obtained in [5] on mass shifting for bosonic string to the case of superstring. The modified anomaly terms of superstring superalgebras are shown and the corresponding BRST charge is used.